Tipburn Severity and Calcium Distribution in Lisianthus (Eustoma Grandiflorum (Raf.) Shinn.) Cultivars under Different Relative Air Humidity Conditions - Takanori Kuronuma; Yua Watanabe; Masaya Ando; Hitoshi Watanabe (Agronomy, 2018)
Tipburn is a major problem for the production of lisianthus (Eustoma grandiflorum (Raf.) Shinn.) cultivars. Relative air humidity is regarded as a key environmental factor affecting tipburn severity in commercial crops. However, there are limited studies comparing the occurrence of tipburn and calcium (Ca) distribution in lisianthus cultivars under different relative air humidity conditions. Accordingly, we investigated the effect of relative air humidity on tipburn severity, transpiration rate, and Ca content in seven lisianthus cultivars. Under a high humidity treatment (70%), only two cultivars (“Voyage pink” (VP) and “Azuma-no-kaori” (AK)) showed significantly higher tipburn severity than those under a low humidity treatment (50%), which suggests that high humidity conditions do not always increase tipburn severity in lisianthus. Transpiration rates of all cultivars, except for AK, were either significantly lower under the high humidity treatment than under the low humidity treatment, or did not vary significantly between the treatments. In contrast, total Ca concentrations in all cultivars, except for “Piccolosa snow” (PS), were significantly higher under the high humidity treatment than under the low humidity treatment. These results suggest that Ca acquisition and distribution in lisianthus cultivars are strongly influenced by Ca uptake from root pressure.